The correct answer is C.
Step 1: -2(6) - 7 = -12 - 7
Step 2: -12 - 7 = -19
Young checked his answer by substituting z=6 back into the original equation and simplifying to make sure both sides are equal.
young solves the equation -2z - 7 = 19 and gets z=6. Which answer best shows how he checked his answer? Find the right answer
A. Step 1: -2(6) - 7
Step 2: -12 - 7
Step 3: -19
B. Step 1: -2(6) - 7
Step 2: 4 - 7
Step 3: -4
C. Step 1: -2(6) - 7
Step 2: -12 - 7
Step 3: -5
D. Step 1: -2(6)-7
Step 2: 12 - 7
Step 3: 5
1 answer